The efficacy and safety of haloperidol for the treatment of delirium in critically ill patients: a systematic review and meta-analysis of randomized controlled trials - Huang, Jian; Zheng, Hui; Zhu, Xianfeng; Zhang, Kai; Ping, Xiaofeng (Frontiers in Medicine, 2023)
Purpose: Delirium is common during critical illness and is associated with poor outcomes. Therefore, we conducted this meta-analysis to investigate the efficacy and safety of haloperidol for the treatment of delirium in critically ill patients. Methods: Randomized controlled trials enrolling critically ill adult patients to compare haloperidol with placebo were searched from inception through to February 20th, 2023. The primary outcome were delirium-free days and overall mortality, secondary outcomes were length of intensive care unit stay, length of hospital stay, and adverse events. Results: Nine trials were included in our meta-analysis, with a total of 3916 critically ill patients. Overall, the pooled analyses showed no significant difference between critically ill patients treated with haloperidol and placebo for the delirium-free days (MD -0.01, 95%CI -0.36 to 0.34, P=0.95, I2=30%), overall mortality (OR 0.89, 95%CI 0.76 to 1.04, P=0.14, I2=0%), length of intensive care unit stay (MD -0.06, 95%CI -0.16 to 0.03, P=0.19, I2=0%), length of hospital stay (MD -0.06, 95%CI -0.61 to 0.49, P=0.83, I2=0%), and adverse events (OR 0.90, 95%CI 0.60 to 1.37, P=0.63, I2=0%). Conclusions: Among critically ill patients, the use of haloperidol as compared to placebo has no significant effect on delirium-free days, overall mortality, length of intensive care unit and/or hospital stay. Moreover, the use of haloperidol did not increase the risk of adverse events.